Examining Self and Finding a Healing Path: Internalized Racism and Intersectionality of a Thai Mother-Scholar - Chaomuangkhong, Tipsuda (Journal of the Motherhood Initiative for Research and Community Involvement, 2022)
When President Trump called COVID-19 the “Chinese virus,” media outlets picked up the term and spread it like wildfire. Many Asian Americans experienced both verbal and physical abuse and an unprecedented rate of discrimination towards them in places that used to be more inclusive. A sixty-seven-year-old Asian woman got brutally attacked in New York City for just being Asian—an incident that revealed to Asian people that the United States (US) no longer welcomed them. These anti-Asian hate crimes combined with postpartum depression (PPD) made me emotionally ill. Desperate for uplift, I took on expressive writing as a therapeutic tool to cope with the childbirth trauma, oppression, and racism I experienced. Through rounds of thematic analysis, I used four different themes to restory the critical events: 1) my earlier racial identity: colourism in Thai and American cultures; 2) (denied) access to spaces: immigrating while Asian; 3) being silenced during labour; and 4) baby love leads to (Asian) self-love. This article examines the role of internalized racism and racial inequity that a Thai mother-scholar experiences while immigrating, settling, and giving birth in the US.